Development of alternative micro and nanoparticulate polymeric systems for mucosal delivery of Streptococcus equi antigens - Florindo (2008)
Tese de doutoramento em Farmácia (Tecnologia Farmacêutica), apresentada à Universidade de Lisboa através da Faculdade de Farmácia, 2008